Analisis Keamanan Produk Saus Sambal Non-BPOM Berdasarkan Uji Cemaran Kimia dan Mikrobiologi yang Ditemukan di Pasar Kranji, Kota Bekasi: Analysis of Bacterial and Chemical Contamination in Non-BPOM Licenced Packaged Chili Sauce Found in Kranji Market, Bekasi City - Michael Dayln Silalahi; Ahsanal Kasasiah; Aliya Azkia Zahra (Bachelor of Pharmacy Study Program, Faculty of Health Sciences, Universitas Singaperbangsa Karawang, 2025)
Several studies have shown that sauces circulating on the market still contain microbial contamination exceeding the threshold and dangerous dyes such as Rhodamine B. This study highlights the importance of education for producers to take care of BPOM licensing in order to increase consumer confidence and product safety. This study aims to evaluate the safety of non-BPOM packaged chili sauce products sold in the Kranji market. Bekasi City, with a focus on microbial contamination and the content of dangerous dye Rhodamine B. Microbial tests were carried out using the Total Plate Count (TPC) method based on BPOM standard No. 13 of 2019, while the Rhodamine B content was analyzed using Thin Layer Chromatography (TLC). The results showed that all samples tested met BPOM microbiological safety standards with the number of colonies not exceeding 10⁴ colonies/g and no Rhodamine B was found in the samples tested for stain observations on TLC. With these results, the products tested can be said to be safe for consumption even though they do not yet have a BPOM licensing. Keywords: sauce; chili; rhodamin B; contamination; TPC.